2022
DOI: 10.3390/foods11091181
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Rice Quality Traits Using Low-Cost Digital Technologies

Abstract: Aroma and other physicochemical parameters are important attributes influencing consumer perception and acceptance of rice. However, current methods using multiple instruments and laboratory analysis make these assessments costly and time-consuming. Therefore, this study aimed to assess rice quality traits of 17 commercial rice types using a low-cost electronic nose and portable near-infrared spectrometer coupled with machine learning (ML). Specifically, artificial neural networks (ANN) were used to classify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…On the other hand, MG811 was the sensor sensitive to carbon dioxide and had the highest FL in PC2. These results reflect those of a prior study by Aznan et al [11], who also found significant positive correlations (p < 0.05) between MQ137 and volatile compounds found in raw rice, such as the valeric anhydride (r = 0.53), nonanal (r = 0.49), and octanoic acid (r = 0.54). Octanoic acid is a short-chain fatty acid found in raw rice that was developed through the oxidation of linoleic acid over the storage period [31], while nonanal is one of the major VOCs that contribute to the rice aroma associated with aldehydic, fatty, waxy, citrus, and floral aromas [32].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, MG811 was the sensor sensitive to carbon dioxide and had the highest FL in PC2. These results reflect those of a prior study by Aznan et al [11], who also found significant positive correlations (p < 0.05) between MQ137 and volatile compounds found in raw rice, such as the valeric anhydride (r = 0.53), nonanal (r = 0.49), and octanoic acid (r = 0.54). Octanoic acid is a short-chain fatty acid found in raw rice that was developed through the oxidation of linoleic acid over the storage period [31], while nonanal is one of the major VOCs that contribute to the rice aroma associated with aldehydic, fatty, waxy, citrus, and floral aromas [32].…”
Section: Resultssupporting
confidence: 90%
“…Compared to GC-MS analysis, an e-nose provides rapid detection to obtain results in a few seconds or minutes. Previous studies in rice have shown the reliability of e-nose applications such as analyzing the volatile compounds in rice [11], distinguishing expired and non-expired rice [12], monitoring rancidity and insect infestation in brown rice [13], detecting fungal infection in jasmine brown rice [14], and identifying moldy rice [15]. In rice adulteration, Udomkun et al [16] assessed the feasibility of a commercial e-nose paired with principal component analysis (PCA) to identify the degree of adulteration in Thai jasmine rice in storage conditions.…”
Section: Introductionmentioning
confidence: 99%
“…PLSR and PCR were combined with the NIR spectra for the evaluation of the hardness and toughness of cooked parboiled rice, respectively [22]; however, the models were only applicable for screening and approximate calibration. The artificial neural networks (ANNs) combined with the NIR spectra of raw rice provided a model with a high R = 0.94; this combination could estimate the color, texture, and pH of cooked rice, offering a rapid and cost-effective method [23]. Together, these findings highlight the potential of digital technologies, artificial intelligence, and spectroscopy to enhance rice quality assessment efficiently and precisely.…”
Section: Introductionmentioning
confidence: 91%
“…The back extrusion (BE) test rig developed by researchers in the Asian Institute of Technology has been used for measuring the hardness of cooked rice [33,36,37], and the BE instrument could best interpret the sensory hardness-softness texture of cooked rice [36]. The BE testing of the textural properties of cooked GBR rice showed a high measurement precision in the hardness, toughness, and stickiness tests, respectively [23]. Therefore, we used the BE for our experiment.…”
Section: Back Extrusion Test For Texture Of Cooked Gbrmentioning
confidence: 99%
See 1 more Smart Citation